2020
DOI: 10.1186/s12886-020-01677-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional assessment of early retinal changes in diabetic patients without clinical retinopathy using multifocal electroretinogram

Abstract: Background We aimed to assess early retinal changes in diabetic subjects without clinical retinopathy using multifocal electroretinogram (mfERG). Methods Twenty eyes of 20 diabetic subjects type 2 without retinopathy and 20 eyes of 20 healthy controls of the same age and sex were eligible for our study and underwent mfERG. MfERG responses were recorded; N1–P1 amplitude and P1 implicit time of the 5 rings recorded were measured and analyzed. Results The reduction in N1–P1 amplitude and the delay in P1-impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
(24 reference statements)
1
6
0
1
Order By: Relevance
“…These findings are observed in the absence of significant alterations to the macular thickness, RNFL, GCL + IPL thicknesses or clinical signs of DR. Previous studies 20 23 have demonstrated a reduction in P1 amplitudes and a delay in latencies in subjects with type 2 diabetes without DR compared to healthy controls, with a negative correlation between P1 amplitude and diabetes duration, and a positive correlation between P1 latency and diabetes duration 22 . It is likely that the retinal functional alterations may start in people with prediabetes 24 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These findings are observed in the absence of significant alterations to the macular thickness, RNFL, GCL + IPL thicknesses or clinical signs of DR. Previous studies 20 23 have demonstrated a reduction in P1 amplitudes and a delay in latencies in subjects with type 2 diabetes without DR compared to healthy controls, with a negative correlation between P1 amplitude and diabetes duration, and a positive correlation between P1 latency and diabetes duration 22 . It is likely that the retinal functional alterations may start in people with prediabetes 24 .…”
Section: Discussionmentioning
confidence: 88%
“…These alterations have been linked to complex mechanisms such as increased oxidative stress, inflammation, loss of neuroprotective factors and glutamate excitotoxicity in long-standing diabetes 35 39 . Hyperglycemia is reported to disrupt the metabolic environment in the retina, which affects neuronal survival, leading to early neuronal cell death 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple evidence has pointed out that changing lifestyle, ameliorating insulin resistance, and repairing damaged β islet cell function can effectively delay the occurrence of DR [57][58][59]. DR is now recognized as a neuro-and vaso-degenerative rather than a microvascular disease, even in early stage when neuron loss is not evident [60,61]. Recently, the crucial role of ferroptotic cell death has been noted in various neurodegenerative diseases, especially in Alzheimer's disease and Parkinson's disease, while its role in DR is largely unknown [62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…They should also undergo regular life-long retinal examinations [ 21 ]. In diabetic patients without clinically observable DR, optical coherence tomography angiography (OCTA) is used to interpret vessels of the retina and capillaries parameters [ 22 ]. Systems including photographs use readers in the form of human or artificial intelligence for the detection of the disease.…”
Section: Reviewmentioning
confidence: 99%